Giant Juvenile Fibroadenoma of Breast (Journal of Surgical Sciences, 2019)
Giant juvenile fibroadenoma occurs in adolescent girls. These tumours become enormous in size and grow rapidly, though these tumours are mostly benign. These patients are almost always treated by breast conserving surgery. Here we present a case having unilateral giant juvenile fibroadenoma with bilateral multiple small fibroadenomas in an adolescent female aged 16years. The diagnosis of the patient was made on clinical examination, USG & FNAC. Confirmatory diagnosis was made by histopathology. We removed the giant one with "Swiss-Roll" procedure and others by simple enucleation. The aesthatic appearence of the breasts were preserved.Journal of Surgical Sciences (2013) Vol. 17 (2) : 99-102